Mitigating long-term unemployment in Europe - Hiroaki Miyamoto; Nujin Suphaphiphat (IZA Journal of Labor Policy, 2021)
While unemployment rates in Europe declined after the global financial crisis until 2018/2019, the incidence of long-term unemployment, the share of people who have been unemployed for >1 year to the total unemployed, remained high. Moreover, the COVID-19 pandemic could aggravate the long-term unemployment. This paper explores the factors associated with long-term unemployment in European countries using a panel of 25 European countries over the period 2000-2018. We find that skill mismatches, labor market matching efficiency, and labor market policies are associated with the incidence of long-term unemployment. Among the different types of active labor market policies, training and startup incentives are found to be effective in reducing long-term unemployment.
Keywords: E24; J64; J68; 330; ong-term unemployment; labor market matching efficiency; active labor market policy